Playing tag. (Economist, 2007)
The article focuses on Aka-Aki, a startup company in Berlin, Germany which has created an online social network that can be accessed on cellular telephones and other mobile communication systems. The firm uses Bluetooth technology combined with its own software to allow cellular telephone users to identify other social network members within 20 meters of their location.